A DESCRIPTIVE WRITING MODULE INTEGRATING BANTEN LOCAL WISDOM THROUGH POWTOON AND FLIPPED CLASSROOM STRATEGIES - Litteu Nur El Lailatie,; Endry Boeriswati,; Samsi Setiadi, (Proceeding of International Seminar on Humanity, Education, and Language, 2025)
This study investigates the effectiveness of audiovisual learning media, specifically instructional videos, in enhancing seventh-grade students’ understanding and ability to write descriptive texts that incorporate Banten local wisdom. The developed product is a Powtoon-based instructional video presenting key concepts of descriptive texts. Implemented through a flipped classroom approach, the video is shared via WhatsApp to allow students to independently explore the material prior to in-class instruction. The research adopts the Research and Development (R&D) method, aimed at designing, testing, and refining educational products. Findings indicate that audiovisual media accommodate diverse student learning styles and promote greater engagement through accessible and relevant content. Moreover, the flipped classroom model fosters student autonomy, allowing them to acquire foundational knowledge before deeper classroom discussion. This approach demonstrates potential for improving both the quality and efficiency of learning descriptive texts in junior high school settings.